Profile of Hematocrit Level Captured by Digital Hematocrit Test - Widiyanti, Prihartini; Sardjono, Tri Arif (Indonesian Journal of Tropical and Infectious Disease, 2015)
The dengue fever is a disease caused by Dengue virus which is transmitted via Aedes aegypti and Aedes albopictus vector. This Dengue Haemorrhagic Fever (DHF) case in Indonesia tend to rise from year to year caused by delayed detection and inadequate handling. The laboratory parameter of hematocrite had regularly been performed using invasive method by taking the blood from the patient. This method is still not been able to monitor patients with DHF by repetitive and accurate measurament. This research project aims is to perform a digital hematocrit test (DHT) with non-invasive accurate sensors. Digital Hematocrit Test (DHT) is needed to presenting fast, exact, economical and accurate detection methods of hematocrit level. Measureable magnitude by the instrumentation is non-absorb intensity electromagnetic waves 560 nm emitted by transmitter captured by receiver. Signal captured by the receiver then converted into electrical signal. The electrical signal from receiver was the levels of hemoglobin. Levels of hemoglobin then converted to hematocrit. Hematokrit is three times the level of hemoglobin. Technology of hematocrit monitoring is aimed to control DHF patient clinical symptoms continuously and acquisitively.